Elastomers for waterworks : pipes, valves, and fitting - Ballun, John V. (AWWA manual ;, 2020)
"This manual presents the history and general application of elastomers in waterworks pipes, valves, and fittings. The principles used for evaluating, selecting, testing, and maintaining various seals will be presented"--